Developing Handbook of Job-Embedded Professional Development to Improve Social Presence for Teacher in Post Covid-19 Era - Rodhiyya, Zaenab Amatillah; Putra Bhakti, Caraka (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
The Covid-19 pandemic is a challenge for teachers to be able to organize an interactive online learning process. Various problems arise in online learning, such as lack of motivation, one-way communication, an excessive amount of assignments, and low competencies and technological skills of teachers. From these problems, the authors offer an idea in the form of handbook of Job-Embedded Professional Development that will equip teachers with social presence skills. This article was compiled using the Research and Development method with a 4D model consisting of Define, Design, Development, and Dissemination. It has reached the Development stage and ready to be developed to Dissemination stage. The JEPD Model handbook is considered to increase teacher’s social presence because the training is attached to schools with flexible hours to accommodate all teachers. The training consists of 7 sessions with 56 hours of training duration and needs supervision from the stakeholders to be optimal. Keywords: teacher, JEPD, training, social presence